PENERAPAN POLA PERKULIAHAN MUHADATSAH MELALUI METODE DEBAT AKTIF PADA PRODI PENDIDIKAN BAHASA ARAB FAKULTAS TARBIYAH DAN KEGURUAN UIN AR-RANIRY BANDA ACEH - Tarmizi TN Ninoersy; Saiful Akmal (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2020)
The study is entitled The Application of Arabic Conversation Lecture Patterns in the Department of Arabic Language Education, UIN Ar-Raniry Banda Aceh Through Active Debate Method. It is aimed at understanding the level of effectiveness of the method, knowing students‘ ability in Arabic conversation class towards student-centered learning, and finding the obstacles encountered in the transformation of lecture patterns in Arabic Conversation Class. This study used quantities quasi-experimental design with control group as well as a pre-test and post-test mechanisms combined with statistical analysis to look for the effects of certain treatments under controlled conditions. There are two variables in this study, namely the independent variable in the form of the use of the active debate method and the dependent variable in the form of Arabic conversation‘ student. The population of this study students’ representation from the incoming 2018-2019 batch totaling 205 students. The sampling technique applied was random sample sampling with the number of samples in this study were 53 students from units 02 and 07. Data collection techniques employed were observation, experiment, interview, and document study. Data analysis in this study was carried out repeatedly with data reduction systems, data presentation, and verification or conclusion drawing. The calculation results show the level of student ability is 83.13%, this shows that the active debate method is very effective in lecturing Muhadatsah. Findings also showed that the active debate usage in Arabic conversation classroom only causing averagely 9, 52 percentage of obstacles namely: understanding the problem, understanding the intention, and controlling emotion.